Craniomandibular Disorders and Mandibular Reference Position in Orthodontic Treatment - Farid Bourzgui; Hakima Aghoutan; Samir Diouny (Hindawi Limited, 2013)
The aim of this paper is to bring into focus the literature on the choice of the mandibular reference position in orthodontic treatment; of a particular reference to this paper is intercuspal position, centric relation position, or therapeutic position. To give a comprehensive account of the literature review on craniomandibular disorders (CMD), we have relied on books and articles using both Google Scholar and PubMed. Selection criteria included a combination of Mesh and type of article. Article classification was made by two authors, using the following structure outline: prevalence of craniomandibular disorders, its etiology and pathophysiology, occlusion and craniomandibular disorders, orthodontic treatment and CMD, and the mandibular reference position in orthodontics. An important conclusion that emerged from the present literature review is that CMD do not seem to be directly related to orthodontic treatment, and their appearance cannot be predicted or prevented by any means. Therefore, orthodontists must adopt a mandibular reference suitable to their patients and which best respects the balance existing in the stomatognathic system.